Consumer Styles of the Saint-Petersburg Middle Class: from the Economy of Deficit to New Way of Life - ГладаревБорис Сергеевич; ЦинманЖанна Михайловна (Journal of Economic Sociology, 2010)
The paper is devoted to the analysis of the peculiarities of the consumer behavior of the representatives of the Russian middle class (on example of Saint-Petersburg). The authors focus on the role of individual consumer strategies in the production of remarkable socio-economic transformations and try to classify the specific characteristics of consumer behavior of post soviet middle class representatives. The first part of the paper determines the main definitions and analyzes consumer style under the conditions of post soviet economy as well as provides the hypotheses for the reasons of plan economy collapse. The second part is devoted to the analysis of the life style transformation and depicting of the peculiarities of consumer styles of Saint-Petersburg middle class under the market economy. The third part considers the leisure activities of the middle class and everyday life consumption practices of the essential commodities. The authors conclude that the transition of consumer styles of post soviet middle class has not finished yet. At the end of the paper the authors give the link between the micro-level of individual consumer styles and the macro-level of national socio-economic transformation of the last 20 years